Secondary Intention Healing After Functional Surgery for in Situ or Minimally Invasive Nail Melanoma - Gwanghyun Jo; Keunyoung Hur; Soo Ick Cho; Je-Ho Mun (Medical Journals Sweden, 2020)
Abstract is missing (Short communication)